HUBUNGAN KARAKTERISTIK DEMOGRAFI DENGAN PENGETAHUAN MASYARAKAT TENTANG PENYAKIT HEPATITIS DI RW 07 KELURAHAN JATINEGARA JAKARTA TIMUR - Siti Aisyah; Farida Tuahuns; Rawati Sianturi (Jurnal Farmasi IKIFA, 2024)
Hepatitis is commonly known as jaundice. It is an inflammation of the liver that can be caused by viral infections, metabolic disorders, drugs, alcohol and parasites. In Indonesia, hepatitis has become one of the diseases that receive serious attention. This is related to Indonesia's large population and its complexity, increasing cases of obesity, diabetes mellitus and hyperlipidemia also have consequences for the onset of liver complications such as hepatitis. Few people know that hepatitis is a medical problem that must be treated immediately. This mindset is based on beliefs that are still related to the culture of divination. This study aims to determine the description of public knowledge about hepatitis in RW 07 Jatinegara Village, East Jakarta in March 2024. The method used in this research is quantitative descriptive method. There were 359 samples in this study obtained by Propotional Random Sampling technique. The results of public knowledge in RW 07 Jatinegara Village, East Jakarta were in the good category as many as 143 respondents (40%), the sufficient category as many as 164 respondents (46%), and the poor category 52 respondents (14%). It can be concluded that public knowledge about hepatitis in RW 07 Jatinegara Village, East Jakarta is in the moderate category as many as 164 respondents (46%).